2020
DOI: 10.3390/microorganisms8101457
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Helicobacter pylori Eradication Therapy on Platelet Recovery in Pediatric Immune Thrombocytopenic Purpura-Case Series and a Systematic Review

Abstract: Evidence relating to the efficacy of Helicobacter pylori eradication therapy for chronic immune thrombocytopenic purpura (cITP) in childhood is inadequate. The aim of this retrospective study was to determine the efficacy of H. pylori eradication therapy for platelet response in pediatric patients with cITP in our hospital, and to perform a systematic review of previous reports about pediatric patients with cITP who were positive for H. pylori infection and were treated with H. pylori eradication therapy. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Other combinations for eradication therapy, such as concomitant therapy, hybrid and high dose dual therapy have all been used as first-line therapies [34,35]. Some gastrointestinal symptoms, such as reflux symptoms, maldigestion or abdominal pain, and hematologic diseases, such as iron deficiency or thrombocytopenia purpura, may be relieved after eradication therapy [36]. To overcome the varying potency of PPIs interfered by CYP2C19 genotypes, several studies used a potassium-competitive acid blocker, P-CAB, such as vonoprazan for H. pylori eradication combination therapy [37].…”
Section: Discussionmentioning
confidence: 99%
“…Other combinations for eradication therapy, such as concomitant therapy, hybrid and high dose dual therapy have all been used as first-line therapies [34,35]. Some gastrointestinal symptoms, such as reflux symptoms, maldigestion or abdominal pain, and hematologic diseases, such as iron deficiency or thrombocytopenia purpura, may be relieved after eradication therapy [36]. To overcome the varying potency of PPIs interfered by CYP2C19 genotypes, several studies used a potassium-competitive acid blocker, P-CAB, such as vonoprazan for H. pylori eradication combination therapy [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, platelet response rates seem to be higher in patients with milder thrombocytopenia and countries with higher prevalence of H. pylori infection [81]. One previous systematic review of studies performed on pediatric populations concluded that platelet response rates in pediatric populations are expected to be similar to the ones found so far in adults and that H. pylori eradication should constitute a first-line treatment approach in children with ITP as well [82]. There is still a discrepancy between the results reported by cohort studies, such as those included in the review, and individual case reports which sustain the need for H. pylori infection eradication in pediatric ITP.…”
Section: Discussionmentioning
confidence: 90%
“…As shown in the first randomized research in Latin America, it is of significant importance to examine whether the children and adolescents with ITP are infected with H. pylori when dealing with the disease; the PLT count is obviously higher in patients who get treated (121). Data from 706 children in 18 previous reports showed a H. pylori infection rate of 23% and a platelet response rate of 43.8%, and the effect of H. pylori eradication in children is the same as that in adults (122). Some scholars treated pregnant women for H. pyloripositive ITP after purging H. pylori.…”
Section: Immune Thrombocytopenic Purpuramentioning
confidence: 99%